Tuberculosis treatment outcome monitoring in England, Wales and Northern Ireland for cases reported in 2001. Issue 4 (19th March 2007) - Antoine, Delphine; French, Clare E; Jones, Jane; Watson, John M
Abstract : Background: Tuberculosis treatment outcome monitoring was introduced in England, Wales and Northern Ireland in 2002 based on cases reported in 2001. Objective: To estimate the proportion of treatment success and to identify predictors of non-completion for cases reported in 2001. Method: At 12 months after the start of treatment, outcome was assessed according to a protocol based on standardised European recommendations. Results: The proportion of cases completing treatment by 12 months was 79% if calculated for cases in whom outcome information was reported, and 62% of all cases regardless of whether information on outcome was reported or not. Of the new smear-positive pulmonary cases for whom information on outcome was reported, 77% completed treatment. Non-completion of treatment was associated with male sex, age ⩾65 years, recent entry into UK for those born abroad, residence outside London, pulmonary disease and drug resistance. Conclusions: Despite the resources of an industrialised country with a low incidence of tuberculosis, the World Health Organization treatment success target of 85% was not achieved. This was partly due to the number of deaths in the elderly, and partly due to missing outcome information for 21% of the cases. As in other low-incidence countries, additional outcome measures such as the proportion of those aged <65 years completing treatment would provide a more comparable indicator for assessment of treatment success. This first year of data collection has shown the importance of increasing the proportion of cases for whom outcome is ascertained, and of ensuring the validity of information provided.